2021
DOI: 10.1111/joa.13584
|View full text |Cite
|
Sign up to set email alerts
|

Typical m. triceps surae morphology and architecture measurement from 0 to 18 years: A narrative review

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Muscle ultrasonography is increasingly used to improve the understanding of musculoskeletal impairments in children with spastic Cerebral Palsy (SCP) (Williams et al ., 2021). During growth, adaptations in skeletal muscles, i.e., an increase in muscle length and anatomical cross-sectional area (aCSA), resulting in increasing muscle volume, occur in both typically developing (TD) children and children with SCP (Benard et al ., 2011; Modlesky and Zhang, 2019; Bell et al ., 2021; Handsfield et al ., 2022). However, these increases are lower in children with SCP compared to TD children (Barber et al ., 2016), while muscle tendons were found to be longer (Barrett and Lichtwark, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Muscle ultrasonography is increasingly used to improve the understanding of musculoskeletal impairments in children with spastic Cerebral Palsy (SCP) (Williams et al ., 2021). During growth, adaptations in skeletal muscles, i.e., an increase in muscle length and anatomical cross-sectional area (aCSA), resulting in increasing muscle volume, occur in both typically developing (TD) children and children with SCP (Benard et al ., 2011; Modlesky and Zhang, 2019; Bell et al ., 2021; Handsfield et al ., 2022). However, these increases are lower in children with SCP compared to TD children (Barber et al ., 2016), while muscle tendons were found to be longer (Barrett and Lichtwark, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Muscle ultrasonography is increasingly used to improve the understanding of musculoskeletal impairments in children with spastic Cerebral Palsy (SCP) (Williams et al, 2021). During growth, adaptations in skeletal muscles, namely an increase in muscle length and anatomical cross‐sectional area (ACSA), resulting in increases muscle volume, occur in both typically developing (TD) children and children with SCP (Bell et al, 2021; Benard et al, 2011; Handsfield et al, 2022; Modlesky & Zhang, 2019). However, these increases are lower in children with SCP compared to TD children (Barber et al, 2016), while tendons are found to be longer (Barrett & Lichtwark, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of growth rates in typically developing children may have implications for understanding disordered growth, for example, in children with neurological disorders such as cerebral palsy. Currently, it is largely unknown if growth rates differ between muscles, because most studies of muscle growth in childhood have investigated only one muscle (Bell et al, 2021;Benard et al, 2011;Binzoni et al, 2001;De Beukelaer et al, 2023;D'Souza et al, 2019;Herskind et al, 2016;Morse et al, 2008;Walhain et al, 2023;Weide et al, 2015Weide et al, , 2020 or a few muscles (Böl et al, 2017;Handsfield et al, 2022;Modlesky & Zhang, 2020;Mogi & Wakahara, 2022;O'Brien et al, 2010;Peeters et al, 2023;Siebert et al, 2017;Williams et al, 2022;Yanagisawa et al, 2014). O'Brien et al (2010) reported that the four components of the quadriceps muscles undergo similar relative increases in volume from childhood to adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Most in vivo measurements of human muscle volumes have been conducted using three‐dimensional ultrasound imaging (Bell et al., 2021 ; Peeters et al., 2023 ; Walhain et al., 2020 ; Weide et al., 2020 ; Williams et al., 2021 ) but ultrasound imaging is more difficult with deep muscles so its application in studies of muscle growth has been largely limited to superficial muscles. Some studies have used magnetic resonance imaging (MRI; Bell et al., 2021 ; D'Souza et al., 2019 ; Handsfield et al., 2014 ; Handsfield et al., 2016 ; Handsfield et al., 2017 ; Morse et al., 2008 ; Noble et al., 2014 ; Noble et al., 2017 ; O'Brien et al., 2010 ; Oberhofer et al., 2010 ; Pitcher et al., 2018 ; Vanmechelen et al., 2018 ; Yanagisawa et al., 2014 ) making it possible to measure the volume of all muscles. Even so, most MRI studies have analysed only a small number of muscles because the process of manually segmenting many muscles from a single participant, or of just one or two muscles from a large cohort, is very time‐consuming (Domroes et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%